Telomere length in white blood cell DNA and lung cancer: a pooled analysis of three prospective cohorts - Seow, Wei Jie; Cawthon, Richard M; Purdue, Mark P; Hu, Wei; Gao, Yu-Tang; Huang, Wen-Yi; Weinstein, Stephanie J; Ji, Bu-Tian; Virtamo, Jarmo; Hosgood, 3rd, H Dean; Bassig, Bryan A; Shu, Xiao-Ou; et al. (Cancer research (Chicago, Ill.), 2014)
We investigated the relationship between telomere length and lung cancer in a pooled analysis from three prospective cohort studies: the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, conducted among men and women in the United States, and previously published data from the Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) Trial conducted among male smokers in Finland, and the Shanghai Women's Health Study (SWHS), which is comprised primarily of never-smokers. The pooled population included 847 cases and 847 controls matched by study, age, and sex. Leukocyte telomere length was measured by a monochrome multiplex qPCR assay. We used conditional logistic regression models to calculate ORs and their 95% confidence intervals (CI) for the association between telomere length and lung cancer risk, adjusted for age and pack-years of smoking. Longer telomere length was associated with increased lung cancer risk in the pooled analysis [OR (95% CI) by quartile: 1.00; 1.24 (0.90-1.71); 1.27 (0.91-1.78); and 1.86 (1.33-2.62); P trend = 0.000022]. Findings were consistent across the three cohorts and strongest for subjects with very long telomere length, i.e., lung cancer risks for telomere length [OR (95% CI)] in the upper half of the fourth quartile were 2.41 (1.28-4.52), 2.16 (1.11-4.23), and 3.02(1.39-6.58) for the PLCO trial, the ATBC trial, and the SWHS, respectively. In addition, the association persisted among cases diagnosed more than 6 years after blood collection and was particularly evident for female adenocarcinoma cases. Telomere length in white blood cell DNA may be a biomarker of future increased risk of lung cancer in diverse populations.